(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
With the sudden change in the learning system due to the pandemic, most students are still adjusting and adapting to online learning. The students have a variety of responses when it comes to online learning systems. Second-year college students experience their college journey through online learning, and they’re still starting to bloom now. In line with this, students are vulnerable to procrastination and stress that may affect their self-efficacy. Students must know how to maintain and uplift their self-efficacy during different situations. The present study aimed to determine the factors affecting online educational platforms and their effect on self-efficacy among second-year college students. The research sample of 366 respondents was randomly selected from second-year students with different courses at Bestlink College of the Philippines. The researchers used the Procrastination Scale, Perceived Stress Scale, and General Self-Efficacy Scale to collect the data. Data were analyzed and presented in frequency, percentage, verbal interpretation, and ranking. For the significant effect of factors affecting students’ self-efficacy in online educational platforms, the researchers analyzed the data using 2-way ANOVA. The results showed that the procrastination and stress of students have a significant effect on their self-efficacy. In line with the outcome, the researchers developed an action plan that will serve as a guide to prevent, maintain and uplift their self-efficacy during and after they study, which may also help them in the future. Lastly, this study revealed that students’ procrastination and stress significantly impact their self-efficacy regarding online educational platforms. The students can carry out necessary actions that lead to better academic performance.